The Impact of Training and Transformational Leadership on Performance with Job Satisfaction as a Mediating Variable (A Case in Unit Pelaksana Teknis Yogyakarta) - Laras, Titi; Jatmiko, Bambang; Astoto, Andrea; Luthfiana, Della Nanda; Cintawati, Handarini (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2023)
The Correctional Division of the Ministry of Law and Human Rights DI Yogyakarta is divided into several Correctional Unit Pelaksana Teknis Yogyakarta consists of 5 units, namely Yogyakarta Class IIA Prison, Yogyakarta Class IIA Women's Prison, Yogyakarta Class IIA State Detention Center, Class I State Confiscated Goods Storage House. The sample in this study was 120 employees, who were recruited using a sampling technique with probability sampling and a stratified random sampling method. The findings revealed that training and transformational leadership positively and significantly affected job satisfaction and performance. Job satisfaction served as a moderating variable between training and transformational leadership on performance. According to the findings of this study, Unit Pelaksana Teknis Yogyakarta can improve training and transformational leadership to increase job satisfaction and employee performance.